Thiadiazole-thiazole derivatives as potent anti-tubercular agents: Synthesis, biological evaluation, and In silico docking studies - Samin A. Shaikh; Shivaji R. Labhade; Raju R. Kale; Prajakta Y. Pachorkar; Rohan J. Meshram; Kamlesh S. Jain; Hrishikesh S. Labhade; Dipak D. Bhanushali; Rahul A. More; Charushila K. Nerkar; Santosh S. Chobe; Aniket N. Marathe; et al. (European Journal of Medicinal Chemistry Reports, 2024)
The present study focuses on research findings related to the development and assessment of thiadiazole-linked thiazole derivatives as promising anti-tubercular agents. We present the synthesis data of eleven new compounds (4a-4k) and confirm their structures using spectroscopic techniques. Subsequently, the compounds were screened for their anti-tuberculosis activities against M. tuberculosis H37Ra. The results demonstrated that compounds 3 and 4b exhibited minimum inhibitory concentration (MIC) of 3.90 μg/mL and 7.81 μg/mL, respectively. In-vitro, studies for few compounds exhibited high antioxidant activity against DPPH and OH radical scavengers along with minimal to no cytotoxicity against RBCs which is a promising result. Investigation of molecular docked conformations revealed different molecular interactions such as hydrogen bonds, halogen bonds, and interactions involving Pi electron cloud. The study sheds light on conserved interactions with residues like Met131, Val163, His90 and Gln161 from the tubercular MCAT enzyme. Interestingly, the synthetic chemistry reveals that the employment of tetra-n-butylammonium bromide (TBAB) plays a crucial role for N-butylation and it also expedites the reaction in tetrahydrofuran solvent.